Is fish worth more than meat? – How consumers' beliefs about health and nutrition affect their willingness to pay more for fish than meat. (April 2018) - Morales, L. Emilio; Higuchi, Angie
Highlights: Survey data about beliefs and fish and meat consumption were collected in Peru. Models estimated effects of variables on willingness to pay more for fish than meat. Preference for fish flavor, household income and size affect the payment extra. Beliefs that fish is healthy and nutritious for the family increase the premiums. This study supports the use of campaigns to promote fish consumption. Abstract: Scientific research has demonstrated that fish consumption has positive effects on human health. Consequently, governments have invested resources to promote fish consumption, but does this investment changed consumer preferences so they are willing to pay more for fish than meat? Consumer survey data collected in Modern Metropolitan Lima, Peru, were analyzed to assess the influence of selected variables on consumers' willingness to pay extra for fish over beef, chicken and pork. The results demonstrate that females, older and more educated respondents are more likely to be unwilling to pay premiums for fish respect to meat. In addition, belief factors do not affect the odds of being unwilling to pay more for fish in preference to meat. Household income and years of education are statistically significant variables increasing the willingness to pay more for fish than meat. In contrast, household size reduces the amount consumers could pay extra for fish. A taste preference for fish has a positive effect on the propensity to pay higher prices for fish than meat. Finally, the beliefs that fish is healthy and nutritious for the family positively affect the willingness to pay more for fish than other meats studied. These findings support the use of campaigns to promote fish consumption and suggest that additional information about the health benefits for the family and nutrition derived from eating fish could affect consumers' preferences, and ultimately their willingness to pay.